Integrated Phase-Locking Scheme for SDFT-Based Harmonic Analysis of Periodic Signals - Sumathi, P.; Janakiraman, P.A. (IEEE transactions on circuits and systems. II, Express briefs, 2008)
The sliding discrete Fourier transform splits periodic signals into selected harmonic components, as on-line time functions. Ordinarily, the sampling frequency is equal to the product of the nominal signal frequency and the window width N. However, when the signal frequency drifts, to avoid the phase and magnitude errors, the sampling frequency can be adaptively adjusted using the phase-error itself. An integrated phase-locked loop scheme and its parameters like hold-in, pull-in ranges, lock time, steady-state